Research on the Structure, Design, and Control of a Variable Transmission Ratio for Active Steering Systems in Commercial Vehicles - Yingkai Ma; Zhijun Fu; Xiang Zhang; Dengfeng Zhao (World Electric Vehicle Journal)
In this paper, a variable gear ratio for active steering systems with a double planetary gear configuration is presented to optimize the steering performance of commercial vehicles. First, a variable transmission ratio system with a dual-row planetary gear mechanism is developed in ADAMS/Car, where the steering mechanism’s transmission ratio can be adjusted according to different driving conditions, thereby improving the vehicle’s stability and sensitivity. Second, a new type of dual-inverter permanent magnet synchronous motor (DPMSM) has been designed to solve the power limitation problem in the electric drive steering of commercial vehicles. Finally, the step steering and lane change driving scenarios are chosen for co-simulation using ADAMS/Car and MATLAB to evaluate the proposed method’s effectiveness. The co-simulation results show that the proposed variable transmission ratio and control strategy can effectively improve the steering sensitivity and stability of commercial vehicles.